Human capital in the field of commercialization: assessment of the competencies of technology transfer specialists - Kozhakhmet, S.; Sharbanu, T. (Karagandy University of the name of academician E.A. Buketov, 2025)
This research article examines the crucial role of human capital in the commercialization of scientific research. It highlights the "Valley of Death", the gap between scientific innovations and their market application, especially in countries moving from planned economies to market-oriented structures. The study highlights the need for trained Technology Transfer Specialists (TTP) who serve as intermediaries between academia and industry, facilitating the transformation of research results into commercially viable products and services. These specialists should have a wide range of qualities. The authors analyze the competencies required for TTP, dividing them into basic skills such as technical understanding and intellectual property management, and soft skills including communication and strategic thinking. The study has identified significant gaps in the current TTP competencies in Kazakhstan and highlights the urgent need for specialized training programs. The recommendations include the creation of targeted educational initiatives, reviewing university hiring practices to attract professionals with business acumen, and creating opportunities for continuous professional development. The aim of the study is to increase the efficiency of commercialization offices and, ultimately, contribute to the development of Kazakhstan's innovation ecosystem and economic growth. This study provides a methodological framework for further educational initiatives in the field of technology transfer.
Keywords: human capital; competencies of specialists; hard skills; soft skills; innovation; interrelation between industry and universities